Health state utilities associated with treatment options for acute myeloid leukemia (AML). (3rd June 2019) - Matza, Louis S.; Deger, Kristen A.; Howell, Timothy A.; Koetter, Kimberly; Yeager, Andrew M.; Hogge, Donna; Fisher, Vicki; Louie, Arthur C.; Chung, Karen C.
Abstract: Aims: Acute myeloid leukemia (AML) treatment typically involves remission induction chemotherapy followed by consolidation chemotherapy. New treatments for AML have recently been introduced, including a chemotherapy formulation called CPX-351, which is administered via less time-intensive IV infusion than the standard "7 + 3" continuous infusion regimen of cytarabine plus an anthracycline. The purpose of this study was to estimate utilities that could be used in economic modeling of AML treatment. Materials and methods: In time trade-off interviews, participants from the UK general population valued 12 health states drafted based on literature and clinician interviews. To identify disutility associated with chemotherapy, two types of induction and four types of consolidation were added to an otherwise identical health state describing AML. The decrease in utility when adding these chemotherapy regimens represents the disutility of each regimen. Five additional health states were valued to estimate utilities associated with other AML treatments. Results: Two hundred participants completed interviews. Mean (SD) utilities were 0.55 (0.31) for pre-treatment AML and 0.66 (0.29) for AML in temporary remission. Adding any chemotherapy significantly decreased utility ( p < 0.0001). Induction had a mean disutility of –0.11 with CPX-351 and –0.15 with 7 + 3. Mean disutility for consolidation ranged from –0.03 with outpatient CPX-351 to –0.11 with inpatient 5 + 2. Utilities are also reported for other AML treatments (e.g. transplant, low-intensity chemotherapy). Limitations: One limitation is that the differences in adverse event profiles between the treatment regimens were based on clinician opinion. Future use of CPX-351 in clinical trials or clinical settings will provide additional information on its adverse event profile. Conclusions: While all chemotherapy regimens were associated with disutility, regimens with shorter hospitalization and less time-intensive infusion were generally perceived as preferable. These utilities may be useful in cost-utility models comparing the value of AML treatments.